Evaluation of pectoralis major myocutaneous flap at tertiary care hospital: retrospective study of 60 cases - Parmar, Bhagirathsinh D.; Jha, Sushil; Sinha, Vikas; Meshram, Sonal; Dave, Gavendra P.; Rajpurohit, Bhagwansingh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Reconstruction following advanced oral cancer is a formidable task in developing country, with poor infrastructure and heavy chunk of advanced stage (T3-T4) oral malignancy. Options available for reconstructions are regional pedicle flaps and microvascular free flaps. Pedicle flaps particularly the pectoralis major myocutaneous (PMMC) flap have an easy learning curve for most of surgeons. Pectoralis major myocutaneous flap is regarded as the workhorse for reconstruction in many head and neck surgeries. Methods: A study was undertaken on patients of soft tissue defects of head and neck region after resection of tumor of oral cavity (squamous cell carcinoma). Total 60 patients, who were managed in ENT department, Sir T hospital, Bhavnagar from 2016-19 were included in this study. Results: Gingivo-buccal complex was the most common site observed for oral malignancy and majority of patients were in TNM stage-I, II, III in this study. Apart from total flap necrosis observed in 1 patient, in rest all the patients PMMC flap very well survived with some major/minor, flap related and unrelated complications. Conclusions: The PMMC flap is effective in reconstruction of defect after excision of oral cavity cancers in developing country with heavy chunk of oral cavity cancer patients. In spite of several minor flap related and flap unrelated complications, PMMC flap survival rate is high and total flap necrosis rate is very low.